Az emberi tudat fejlődésének nyomában: Merlin Donald: A Mind So Rare: The Evolution of Human Consciousness - Négyesi, Péter (Iskolakultúra, 2024)
Donald, M. (2001). A mind so rare: The evolution of human consciousness. Norton.